FORMS OF BUSINESS INTEGRATION: VIEW FROM THE POSITIONS OF INSTITUTIONAL THEORY - Elena V. Ustyuzhanina (Вестник Российского экономического университета имени Г. В. Плеханова)
The article analyzes the most popular forms of doing business, such as unitary, divisional, adhocratic, module and network and discusses their advantages and disadvantages. It is grounded that present day Russian practice of integrating science-intensive companies does not take into account either new forms of integration being developed in the world now or positive soviet experience. The author identifies the key drawbacks of organizational structure of big Russian integrated bodies. Scientific novelty of the article implies the use of institutional methodology for the analysis of the practice for creating and managing large institutional complexes. For example, it could be researching possibilities of using different regulatory systems (methods of coordination) of these structures participants.